Mechanisms of hepatitis B virus X protein in progression and drug resistance of hepatocellular carcinoma - Zhou Ping; Zhu Fan (生物医学转化)
Hepatocellular carcinoma (HCC), as a highly prevalent primary liver malignancy, poses a significant global public health challenge. Its persistently high incidence and mortality rates severely impact patients' quality of life and life expectancy. Although chemotherapy and targeted therapies are commonly administered to patients with advanced HCC, their efficacy is often limited by the emergence of drug resistance. Chronic infection with hepatitis B virus (HBV), encoded by the X region of the HBV genome, plays a critical role in the development of HCC. HBx is a multifunctional regulatory protein that not only promotes the malignant transformation of normal hepatocytes but also contributes significantly to the mechanisms underlying drug resistance in HCC. Recent studies have demonstrated that HBx interferes with multiple molecular pathways, including apoptosis, autophagy, epigenetic modification, and drug efflux, thereby facilitating treatment failure.This review focuses on the molecular mechanisms by which HBx promotes HCC progression and mediates drug resistance, aiming to offer novel therapeutic targets and inform future treatment strategies for drug-resistant HBVrelated HCC.